Correlative study of coronary dominance in human cadaveric hearts, foetal hearts and cine angiograms - Usha Kannan; K Jeyapriya; B Amirtha Ganesh; Anbalagan J; Sudha Rao (Wolters Kluwer Medknow Publications, 2014)
Background and aims: The term right or left dominance is used to describe which coronary branch irrigates the diaphragmatic surface of the heart. Since this concept is misleading, now that coronary artery which gives the posterior inter ventricular artery is considered as dominant one. Right coronary block in left dominance and left coronary block in right dominance are prone for less mortality. But right coronary block in right dominance and left coronary block in left dominance are prone for more mortality. In co-dominance either right or left coronary block are prone for less mortality. Hence a thorough knowledge of coronary dominance is essential for interventional cardiologists and cardiothoracic surgeons to plan proper intervention/ surgery for patients with coronary artery disease. The aim of the study was to study and compare the coronary dominance in hearts obtained from adult cadavers (30), still born foetuses (10) and cine angiograms (30) done on symptomatic patients. Materials and methods : Adult and foetal cadaveric hearts were studied by dissection and painting method. Cine angiogram was done though radial /femoral artery. Results and conclusion: Out of 30 adult cadaveric hearts, 26 (86.66%) showed right dominance, 2 (6.66%) left dominance and 2 (6.66%) had co-dominance. Out of 10 foetal hearts, 7 (70%) showed right dominance, 1 (10%) had left dominance, and 2 (20%) had co-dominance. Out of 30 cine coronary angiograms done through radial/femoral artery, 21 (70%) showed right dominance, 5 (16.66%) had left dominance and 4 (13.33%) had co-dominance. These results were compared with similar studies and discussed.